1998
DOI: 10.1017/s1355838298980104
|View full text |Cite
|
Sign up to set email alerts
|

New features of 23S ribosomal RNA folding: The long helix 41–42 makes a “U-turn” inside the ribosome

Abstract: ABSTRACT23S rRNA from Escherichia coli was cleaved at single internucleotide bonds using ribonuclease H in the presence of appropriate chimeric oligonucleotides; the individual cleavage sites were between residues 384 and 385, 867 and 868, 1045 and 1046, and 2510 and 2511, with an additional fortuitous cleavage at positions 1117 and 1118. In each case, the 39 terminus of the 59 fragment was ligated to radioactively labeled 4-thiouridine 59-,39-biphosphate ("psUp"), and the cleaved 23S rRNA carrying this label … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Recently, a similar strategy has been used to incorporate a cross-linking reagent at internal breaks in 16S (41) and 23S rRNA (42) to obtain distance constraints for modeling the rRNAs. Finally, the system described here provides a possible approach to the identification of the molecular interactions involved in domain-domain contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a similar strategy has been used to incorporate a cross-linking reagent at internal breaks in 16S (41) and 23S rRNA (42) to obtain distance constraints for modeling the rRNAs. Finally, the system described here provides a possible approach to the identification of the molecular interactions involved in domain-domain contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Since the distance between the photoactivatable thiocarbonyl function and the target molecule is nearly zero, the recognition site in nucleotide-nucleotide interaction can be definitively determined. Therefore, such detailed studies made it possible to construct the plausible 3D models of functional molecules such as hammerhead ribozymes, U snRNA, and rRNA . In addition, it was also reported that oligonucleotides incorporating thionucleotides were available for photocrosslinking assay of interaction between proteins and nucleic acids .…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of thionucleotides into oligonucleotides by chemical 1a,3a,5b, and enzymatic 4a, methods has been extensively studied. In the chemical method, various oligonucleotides having thio-substituted nucleosides have been prepared by automated synthesis by use of phosphoramidite units in which the thiol function was appropriately protected to avoid side reactions during the 3‘-phosphitylation and the oxidation by iodine after each coupling cycle.…”
Section: Introductionmentioning
confidence: 99%
“…We have decided to investigate the conformation of the 39 major domain of 16S rRNA in ribosome reconstitution buffer, in the absence of ribosomal proteins+ The 39 major domain is involved in several functions of the ribosome (reviewed by Zimmermann, 1996)+ It interacts with mRNA (Juzumiene et al+, 1995;Sergiev et al+, 1997), initiation factor IF2 (Wakao et al+, 1991), and elongation factor G (Wilson & Noller, 1998)+ Helix 34, in the upper part of the domain, contains the binding site of the antibiotic spectinomycin, an inhibitor of translocation (Makosky & Dahlberg, 1987;Bilgin et al+, 1990;Brink et al+, 1994), it interacts with the termination factors (Murgola, 1996;Arkov et al+, 1998), and it is involved in subunit association (Herr et al+, 1979;Baudin et al+, 1989)+ Furthermore, mutations in helix 34 were found to affect translational accuracy (Moine & Dahlberg, 1994;O'Connor et al+, 1997)+ The lower part of the domain contains nucleotides which are involved in the binding of tRNAs at the P site (Moazed & Noller, 1990;von Ahsen & Noller, 1995;Joseph et al+, 1997), and which have been crosslinked to the A-, P-and E-site-bound tRNAs (Döring et al+, 1994)+ Tetracycline, an inhibitor of tRNA binding to the A site, also interacts with this part of the domain (Oehler et al+, 1997)+ To study the conformation of the large rRNA domains, indirect techniques, such as chemical probing and crosslinking, can provide useful information since NMR and X-ray crystallography are still inadequate+ Random crosslinking has been extensively used to study the higher-order structure of rRNAs (Wilms et al+, 1997;reviewed in Baranov et al+, 1998b)+ Site-directed crosslinking has been used by the groups of Brimacombe and Cooperman but results are still scarce (Alexander & Cooperman, 1998 and references therein;Baranov et al+, 1998a)+ The technique developed by Brimacombe and his coworkers involves the site-specific fragmentation of 16S rRNA with RNase H and the addition of a photoreactive nucleotide at the 39 end of the 59 fragment+ Its use is limited by the capacity of the two fragments to be reconstituted into a 30S subunit+ The procedure of the Cooperman group involves the hybridization to a specific portion of rRNA within the ribosome of a complementary photolabeled DNA probe+ However, this technique requires the rRNA portion that is probed to be exposed and single-stranded, and,...…”
Section: Introductionmentioning
confidence: 99%